2014
DOI: 10.1080/14755610.2014.945468
|View full text |Cite
|
Sign up to set email alerts
|

‘So people know I'm a Sikh’: Narratives of Sikh masculinities in contemporary Britain

Abstract: Drawing on empirical research and informed by recent theoretical discussions surrounding faith identities and masculinities, this article examines second and third generation, British born Sikh men's identification to the Sikh faith. In particular, it focuses on the appropriation and use of recognised Sikh symbols amongst young British men who define themselves as Sikh. This article suggests that whilst there are multiple of ways of 'being' a Sikh man in contemporary postcolonial Britain, and marking belonging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…53 This ideal has its maximum expression in the amritdharis or representatives of the khālsā. 54 Gill (2014), following Kalra (2005). pride and manhood particularly for upper-caste Sikh men 55 . Thus the maximum representatives of an honorable masculinity socio-historically constructed 56 are the keshdharis and especially the amritdharis.…”
Section: Gendered Practices In the Construction Of Sikh Subjects In Bmentioning
confidence: 99%
“…53 This ideal has its maximum expression in the amritdharis or representatives of the khālsā. 54 Gill (2014), following Kalra (2005). pride and manhood particularly for upper-caste Sikh men 55 . Thus the maximum representatives of an honorable masculinity socio-historically constructed 56 are the keshdharis and especially the amritdharis.…”
Section: Gendered Practices In the Construction Of Sikh Subjects In Bmentioning
confidence: 99%
“…Debates about masculinity are also relevant to studies of religion and citizenship. A growing literature is emerging on religious men and masculinities, including historical studies of Christianity and masculinity in Northern Europe (Werner 2011), and historical (Delap and Morgan 2013) and contemporary (Gill 2014;Aune 2010;Archer 2001) studies of men and masculinities within different religious traditions in Britain. In her study of early to mid-twentieth century middleclass Anglican men in England, Delap (2013, 137) found that 'the majority [of Anglican men's groups] were invested in reconciling masculinity with qualities of love, compassion and service, which often led to reciprocity with femininities'.…”
Section: Citizenship Gender and Religionmentioning
confidence: 99%
“…As Connell (1995, p.81) states '[m]arginalization is always relative to the authorization of the hegemonic masculinity of the dominant group'. This questions then how far it is possible for Asian men to aspire to or be aligned to hegemonic or normative notions of masculinity (Kalra, 2009;Gill, 2014).…”
Section: Men and Masculinitymentioning
confidence: 99%
“…Key theorists at this time, including Hall (1992), Brah (1996), and in relation to questions of masculinity; Mac an Ghaill (1994), encouraged a consideration of the performative nature of ethnicity and the ways in which ethnic identity is intersectional and experienced in and through other modalities of difference (such as race, gender, class, sexuality, McClintock, 1995). Black feminist literature, particularly looking at izzat (Wilson, 1978) was influential and developed my understanding of the gendered nature of Asian, and specifically Sikh masculinities in the plural (Gill, 2014). Now the wider frame concerning what is more broadly defined as 'Asian masculinity' creates a different socio-political context.…”
Section: Introductionmentioning
confidence: 99%